2020
DOI: 10.1371/journal.pone.0231943
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of Meteorin-like protein in polycystic ovary syndrome: A case-control study

Abstract: Patients diagnosed with polycystic ovary syndrome (PCOS) are at high risk of developing a myriad of endocrinologic and metabolic derailments. Moreover, PCOS is a leading cause of habitual abortion, also known as recurrent pregnancy loss (RPL). Meteorin-like protein (Metrnl) is a newly discovered adipokine with the potential to counteract the metaflammation. This study aimed at determining the associations of serum Metrnl levels with homocysteine, hs-CRP, and some components of metabolic syndrome in PCOS-RPL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 71 publications
2
27
0
2
Order By: Relevance
“…Two case-control studies revealed lower serum Metrnl levels in PCOS patients than in normal controls, contrary to the level change of IR markers, FSH, and an independent correlation between Metrnl and PCOS ( 67 , 68 ). A study from Iran found that serum levels of Metrnl in the infertile PCOS (PCOS-inf) and PCOS with recurrent pregnancy loss (PCOS-RPL) subgroups were significantly lower than in the control group, which remained significant after adjustment for confounding factors but disappeared when compared between the PCOS subgroups.…”
Section: Methodsmentioning
confidence: 85%
“…Two case-control studies revealed lower serum Metrnl levels in PCOS patients than in normal controls, contrary to the level change of IR markers, FSH, and an independent correlation between Metrnl and PCOS ( 67 , 68 ). A study from Iran found that serum levels of Metrnl in the infertile PCOS (PCOS-inf) and PCOS with recurrent pregnancy loss (PCOS-RPL) subgroups were significantly lower than in the control group, which remained significant after adjustment for confounding factors but disappeared when compared between the PCOS subgroups.…”
Section: Methodsmentioning
confidence: 85%
“…The clinical characteristics and biochemical parameters of the study population are shown in Table 1 as reported in previous studies [ 35 , 36 ]. Statistically significant difference was observed between the PCOS, PCOS-infertile, PCOS-RPL women and non-PCOS groups based on age, BMI, insulin and Free T. The levels of TG and LH in the PCOS patients were significantly higher than in the non-PCOS women.…”
Section: Resultsmentioning
confidence: 99%
“…Venous blood was collected from each subject at the early follicular phase of their menstrual cycle. The subjects previously participated in our studies, and some of the data have been used in recent publications [ 28 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study included 120 subjects diagnosed with PCOS, subdivided into 60 PCOS with Recurrent pregnancy loss (PCOS-RPL) and 60 infertile PCOS (PCOS-Inf) and 60 healthy fertile controls, aged 20–40 years with an average of 29.56 ± 4.14 years (published data) [ 28 , 31 , 32 ]. The inclusion criterion included PCOS diagnosis based on the 2003 Rotterdam Criteria [ 33 ], with the exclusion of conditions such as hyperprolactinemia, thyroid diseases, premature ovarian failure, congenital adrenal hyperplasia, Cushing’s syndrome, and adrenal tumors [ 31 ]. Subjects allocated to the PCOS-RPL subgroup are defined as those who simultaneously had more than two consecutive abortions earlier than their 20 th week of gestation [ 34 ].…”
Section: Methodsmentioning
confidence: 99%